"We Need More than Jingles": Discursive practices of resistance in the Nigerian public׳s responses to the rebranding Nigeria campaign. (September 2016) - Adegoju, Adeyemi
Abstract: This article examines the discursive practices of negotiating Nigeria׳s national identity evidenced in media discussions about Nigeria׳s Rebranding programme. Drawing the data from the responses of the Nigerian public to the Rebranding Nigeria programme as contained largely in letters to the editor, readers׳ text messages, and some headlines of features sourced from select Nigerian national dailies and one news magazine, the study explores the appropriation of the discursive practices of resistance such as framing, humour, negotiation of identity, configuration of alternative models, cynicism, parody and some other language games in negotiating Nigeria׳s national self-images. The study applies Fairclough׳s dialectical-relational approach to CDA which is based on the three dimensions of discourse, namely text, discourse practice, and social practice. The study contributes to existing studies on nation branding by bringing to the spotlight micro acts of resistance in nation branding discourse as opposed to nation-state based discourses which such studies have examined. In so doing, it demonstrates transformation of power relations in knowledge formations about national identity construction. It also reveals that schematic discursive practices largely deployed in organisational resistance could be appropriated to meet the contingency of contesting knowledge formations in nation-state discourses by the public. Highlights: Focuses on micro acts of resistance in national identity construction. Examines discursive practices in contesting knowledge formations. Explores appropriation of organisational resistance practices in competing narratives of national identity. Reveals evidence of the relational nature of power in knowledge formations.